PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP MUHAMMADIYAH PROGRAM KHUSUS SURAKARTA - Salsabila Nur Azzahra; Main Sufanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of digital media in Indonesian language learning at Muhammadiyah Junior High School with Special Program in Surakarta. The study used a descriptive qualitative approach with Indonesian language teachers and students in grades VII and VIII as the subjects. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the dominant digital media used in Indonesian language learning were the Learning Management System (LMS), Kahoot, and Quizizz. LMS was used as a medium for delivering material, giving assignments, and managing learning digitally, while Kahoot and Quizizz were used as interactive evaluation and practice media that could increase student motivation, activeness, and involvement in learning. The use of digital media made the learning process more flexible, interesting, and organized because students could access learning materials anytime and anywhere. In addition to providing positive impacts, this study also found several obstacles, such as internet network disruptions, smartphone distractions, device limitations, and differences in student abilities in operating digital media. Teachers provided tutorials on using digital media, increased supervision during learning, and prepared alternative learning methods in case of technical problems. This research shows that the use of digital media positively contributes to the effectiveness of Indonesian language learning in the digital age.